Distinct TERT promoter C228T and C250T mutations in a patient with an oligodendroglioma: A case report. Issue 3 (26th April 2021) - Ishi, Yukitomo; Okada, Hiromi; Okamoto, Michinari; Motegi, Hiroaki; Tanaka, Shinya; Mitsuhashi, Tomoko; Yamaguchi, Shigeru
Abstract : The majority of oligodendroglial tumors harbor mutations in the telomerase reverse transcriptase (TERT) gene ( TERT ) promoter and the isocitrate dehydrogenase 1/2 (IDH1/2) gene (IDH1/2), as well as 1p/19q codeletion. Generally, TERT promoter mutations, C250T and C228T, are mutually exclusive. We present a case of oligodendroglioma harboring both C250T and C228T mutations in TERT promoter. A 38‐year‐old man presented with grand mal seizures and underwent a resection surgery for a left frontal lobe tumor. He was pathologically diagnosed as having oligodendroglioma and was carefully observed. At 48 years of age, he underwent another resection surgery due to tumor regrowth, with the pathological diagnosis of anaplastic oligodendroglioma. Genetic analysis of the initial tumor specimen revealed IDH1 R132H mutation and both C250T and C228T mutations in TERT promoter. Using mutation‐specific primers, two mutations were considered to be distributed in different alleles. In the tumor specimen obtained during the second surgery, IDH1 R132H mutation was detected to be similar to that of the initial specimen; however, only C228T mutation was detected in TERT promoter. The 1p/19q codeletion was detected in both the initial and recurrent tumor specimens. According to the sequencing data from the two tumor specimens, although TERT promoter mutation has been considered to be an early genetic event in the tumorigenesis of oligodendroglial tumors, it is likely that the C250T and C228T mutations in TERT promoter are subclonally distributed in the same tumor specimen of the present case.